Telomere length and elevated iron: The influence of phenotype and HFE genotype. Issue 6 (13th May 2013) - Mainous, Arch G.; Wright, Robert U.; Hulihan, Mary M.; Twal, Waleed O.; McLaren, Christine E.; Diaz, Vanessa A.; McLaren, Gordon D.; Argraves, W. Scott; Grant, Althea M.
<x xml:space="preserve">Abstract</x> Elevated body iron stores are associated with morbidity and mortality due to oxidative stress. Hereditary hemochromatosis, a common condition caused by HFE gene mutations, can lead to excess iron storage and disease but clinical penetrance of HFE gene mutations is low and many people with elevated iron stores lack HFE mutations. We analyzed data from the Hemochromatosis and Iron Overload Screening Study to assess the relationship among HFE genotype (individuals with either homozygous or compound heterozygous status for C282Y and/or H63D HFE mutations were defined as genotype positive, or G+), elevated iron phenotype (individuals exceeding gender‐specific transferrin saturation and serum ferritin threshold levels were considered phenotype positive, or P+), and leukocyte telomere length, a marker of biological aging and cumulative oxidative stress. In unadjusted analyses in comparison to individuals who were G−P−, G+P− were not significantly different (OR 0.74; 95% CI 0.26–2.04), while the G+P+ (OR 2.03; 95% CI 1.15–3.56), and G−P+ (OR 2.24; 95% CI 1.5–3.29) had increased risk of short telomeres (<=25th percentile) rather than long telomeres (>=75th percentile). In analyses adjusting for age, gender, and race/ethnicity, the effect of individuals with elevated iron phenotypes having short telomeres persisted with G+P+ individuals (OR 1.94; 95% CI 1.02–3.72), and G−P+ individuals (OR 2.17; 95% CI 1.39–3.39) being significantly different from the G−P− group. In conclusion, elevated iron phenotype, but not HFE genotype, was associated with shortened telomeres. Further studies will be needed to determine whether telomere length provides a marker for morbidities specifically associated with iron overload. Am. J. Hematol. 88:492–496, 2013. © 2013 Wiley Periodicals, Inc.